LEGAL POLITICS OF UTILIZING VILLAGE FUND ALLOCATION IN TRADITIONAL TOURIST VILLAGE NGADAS, PONCOKUSUMO SUB-DISTRICT, MALANG REGENCY - Maylika Rahmawati, Nadyah (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM IBLAM), 2023)
The Traditional Tourist Village represents one of the innovations implemented by the Ministry of Culture and Tourism. The concept of Traditional Tourist Village is applied in several regions within the Malang Regency, with one notable instance being the Ngadas Traditional Tourist Village in the Poncokusumo Sub-District of Malang Regency. From an administrative perspective, Ngadas Traditional Tourist Village functions as an administrative village that adheres to and practices the customs of the Tengger Tribe. A logical consequence of its administrative status is the allocation of funds from both local and central governments.The Village Fund Allocation (ADD) constitutes one of the funds disbursed by the Local Government to the Village to facilitate its governance functions. The ADD is derived from revenue-sharing funds received by the Local Government from the Central Government, which are then incorporated into the Regional Budget or APBD. Subsequently, these funds are adjusted to account for specific allocations. The integration of village governance with customary practices in Ngadas Traditional Tourist Village significantly influences the utilization of the Village Fund Allocation (ADD). The village government operates under its own distinct structure, while the Tengger Tribe's customary practices are overseen by a designated leader. In Ngadas Traditional Tourist Village, both entities mutually influence each other. Various policies undertaken by the Village Head as the representative of the Village Government are influenced by the